Anti-Corruption Village: A Solution to Preventing Crime of Corruption and Good Governance in Village - Candra, Septa; Fernando, Zico Junius (Fiat Justisia: Jurnal Ilmu Hukum, 2024)
Anti-corruption village is a concrete manifestation of community participation in preventing criminal acts of corruption. Therefore, this research aimed to eradicate corruption in Indonesia from village level serving as an important indicator and responsible for large amounts of funds. By establishing anti-corruption village, funds were more accountable for optimal development. Meanwhile, doctrinal legal research using primary, secondary, and tertiary legal materials was adopted with statute, conceptual, comparative, and futuristic methods. A descriptive-prescriptive nature was used with the examination of the data or materials through content analysis. The results showed that anti-corruption village program initiated by Corruption Eradication Commission (KPK) disseminated the importance of building integrity and anti-corruption values among government and village community. Additionally, this program functioned as a pilot project to prevent corruption and oversee the development of village community.